Nanoscale domains in strained epitaxial BiFeO3 thin Films on LaSrAlO4 substrate - Chen, Zuhuang (2011)
BiFeO3 thin films with various thicknesses were grown epitaxially on (001) LaSrAlO4 single crystal substrates using pulsed laser deposition. High resolution x-ray diffraction measurements revealed that a tetragonal-like phase with c-lattice constant -4.65 Å is stabilized by a large misfit strain. Besides, a rhombohedral-like phase with c-lattice constant -3.99 Å was also detected at film thickness of -50 nm and above to relieve large misfit strains. In-plane piezoelectric force microscopy studies showed clear signals and self-assembled nanoscale stripe domain structure for the tetragonal-like regions. These findings suggest a complex picture of nanoscale domain patterns in BiFeO3 thin films subjected to large compressive strains.